Molybdenum disulfide nanotube-carbon nanotube-polyether-ether-ketone composite material and preparation method thereof
By adding molybdenum disulfide nanotube-carbon nanotube hybrid material to polyether ether ketone, the wear problem of polyether ether ketone in friction parts is solved, and the compression performance, hardness and friction-reduction and anti-wear effect of the material are improved.
Patent Information
- Application Number
- CN202411939011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Polyether etherketone is prone to wear in friction parts such as radial bearings, and has poor friction reduction and wear resistance.
Add molybdenum disulfide nanotube-carbon nanotube hybrid material to polyether ether ketone, and prepare composite materials through hydrothermal reaction and ultrasonic dispersion to improve their compression performance and hardness.
It significantly reduces the average friction coefficient and wear amount of composite materials, improves compression strength and surface hardness, and enhances friction reduction and wear resistance.
Smart Images

Figure CN119735937A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material and a preparation method thereof. Background Art
[0002] At present, polyetheretherketone (PEEK) has been widely used in aerospace, automobile manufacturing, medical equipment and other fields due to its excellent thermal stability, dimensional stability, mechanical strength, chemical stability and processing performance. However, with the rapid development of modern industrial technology, the requirements for material properties are also constantly increasing. For example, when polyetheretherketone is used for friction parts such as radial bearings and bearing bushings, it is easy to wear under load conditions, and the friction reduction and wear resistance effect is poor. Summary of the invention
[0003] In view of the deficiencies of the above-mentioned related technologies, the purpose of the present application is to provide a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material and a preparation method thereof, by adding molybdenum disulfide nanotube-carbon nanotube hybrid material to polyetheretherketone to improve the compression performance and hardness of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material while improving the friction reduction and wear resistance effect.
[0004] On the one hand, the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material using the following technical solution: A molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material is prepared from the following components in parts by weight: 97-99 parts of polyetheretherketone and 1-3 parts of a molybdenum disulfide nanotube-carbon nanotube hybrid material.
[0005] Preferably, the molybdenum disulfide nanotube-carbon nanotube hybrid material is prepared by the following steps: mixing a precursor, a template, an auxiliary solvent and carbon nanotubes and then performing a hydrothermal reaction.
[0006] Preferably, the precursor comprises a molybdenum precursor and a sulfur precursor in a weight ratio of 0.8-0.9:1.
[0007] Preferably, the precursor comprises a molybdenum precursor and a sulfur precursor in a weight ratio of 0.85:1.
[0008] Preferably, the weight ratio of the molybdenum precursor to the carbon nanotubes is 0.5-10:1.
[0009] Preferably, the weight ratio of the molybdenum precursor to the carbon nanotubes is 1-5:1.
[0010] Preferably, the weight ratio of the molybdenum precursor to the carbon nanotubes is 1.18:1.
[0011] Preferably, the weight ratio of the template to the molybdenum precursor is 1:3.7-3.8.
[0012] Preferably, the weight ratio of the template to the molybdenum precursor is 1:3.74.
[0013] Preferably, the auxiliary solvent comprises water, ethanol and oleic acid in a volume ratio of 7-8:2-3:1.
[0014] Preferably, the auxiliary solvent comprises water, ethanol and oleic acid in a volume ratio of 7.5:2.5:1.
[0015] Preferably, the template includes one or more of manganese chloride tetrahydrate, manganese sulfate, and manganese nitrate.
[0016] Preferably, the molybdenum precursor includes one or more of sodium molybdate dihydrate, ammonium molybdate tetrahydrate, potassium molybdate dihydrate and ammonium dimolybdate.
[0017] Preferably, the molybdenum precursor is sodium molybdate dihydrate.
[0018] Preferably, the sulfur precursor includes one or more of thiourea, ammonium thiocyanate and sodium thiosulfate.
[0019] Preferably, the sulfur precursor is thiourea.
[0020] Preferably, the carbon nanotubes include one or both of multi-walled carbon nanotubes and single-walled carbon nanotubes.
[0021] Preferably, the carbon nanotubes are multi-walled carbon nanotubes.
[0022] On the other hand, the present application provides a method for preparing a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material using the following technical solution: A preparation method of a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material comprises the following steps: mixing a molybdenum disulfide nanotube-carbon nanotube hybrid material, polyetheretherketone powder and a solvent, ultrasonically dispersing the mixture and then drying the mixture; ball-milling the mixture and then drying the mixture; and finally hot-pressing the mixture to obtain the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material.
[0023] Preferably, the ball milling speed is 200-400 rpm, and the ball milling time is 3-5 h.
[0024] Preferably, the ball milling speed is 300 rpm and the ball milling time is 4 hours.
[0025] Preferably, the solvent is ethanol, and the ultrasonic dispersion time is 5-40 min.
[0026] Preferably, the solvent is ethanol, and the ultrasonic dispersion time is 15 min.
[0027] Preferably, the temperature of the hot pressing molding is 350-370° C., the pressure is 5-10 MPa, and the holding time is 0.5-1.5 h.
[0028] Preferably, the temperature of the hot pressing molding is 360° C., the pressure is 7 MPa, and the holding time is 1 hour.
[0029] In summary, the present application includes at least one of the following beneficial technical effects: 1. Compared with polyetheretherketone, the average friction coefficient of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material is reduced by 20%-23.73%, the wear loss is reduced by 77.95%-88.95%, the compression strength is increased by 11.08%-23.77%, and the surface hardness is increased by 3.06%-5.36%. The compression performance and hardness of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material are improved while the friction reduction and anti-wear effect are improved; 2. Compared with carbon nanotube-polyetheretherketone composite materials, the average friction coefficient reduction rate of molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials is 11.36%-17.58%, the wear reduction rate is 30.28%-65.05%, the compression strength increase rate is 4.01%-15.90%, and the surface hardness increase rate is 0.60%-2.78%. The compression performance and hardness of molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials are improved while the friction reduction and anti-wear effect is improved; 3. The raw materials of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material of the present application are easy to obtain, the preparation method is simple, the conditions are mild, no special equipment is required, and no high-concentration chemical reagent modification or coupling agent is required to improve the dispersibility of additives. It is green and environmentally friendly while reducing the preparation cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a scanning electron microscope image of the molybdenum disulfide nanotube-carbon nanotube hybrid material in Example 5 of the present application; Figure 2 This is a scanning electron microscope image of the molybdenum disulfide nanoflower-carbon nanotube hybrid material in Comparative Example 3. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to normal conditions or conditions recommended by the manufacturer. The methods used are conventional methods known in the art unless otherwise specified, and the consumables and reagents used are commercially available unless otherwise specified. Unless otherwise specified, the professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the recorded content may also be applied to the present invention.
[0032] The raw materials used in the examples and comparative examples can all be obtained commercially.
[0033] Example 1 Example 1 of the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material, which is prepared by the following steps: Preparation of molybdenum disulfide nanotube-carbon nanotube hybrid material: 0.932g sodium molybdate dihydrate, 1.096g thiourea and 0.249g manganese chloride tetrahydrate are added as molybdenum precursor, sulfur precursor and template agent respectively to an auxiliary solvent (mixed by 30mL water, 10mL anhydrous ethanol and 4mL oleic acid), and vigorously stirred for 30min on a magnetic stirrer at 700r / min, and then 0.1g multi-walled carbon nanotubes (MWCNTs) are added, stirred and ultrasonically treated for 20min to obtain a mixed solution. The mixed solution is poured into a 100mL reactor for hydrothermal reaction, and the reaction parameters are as follows: heating to 210°C at a rate of 1°C / min, maintaining the temperature for 12h, and then slowly cooling to room temperature at a rate of 0.4°C / min, filtering and washing to obtain a molybdenum disulfide nanotube-carbon nanotube hybrid material.
[0034] Preparation of MoS2 nanotube-CNT-PEEK composite material: Accurately weigh 98g PEEK powder and 2g MoS2 nanotube-CNT hybrid material. Add the PEEK powder and MoS2 nanotube-CNT hybrid material into ethanol, ultrasonically disperse for 15min and place on a magnetic stirrer, stir at 600rpm for 3h, then dry at 80℃ for 4h and at 100℃ for 2h to obtain a mixture. Add the mixture into a ball mill and ball mill at 300rpm for 4h, then dry in a drying oven at 120℃ for 3h to obtain a mixture, place the mixture in a mold, maintain pressure at 360℃ and 7MPa for 1h, and hot press to obtain a MoS2 nanotube-CNT-PEEK composite material.
[0035] Example 2 Example 2 of the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material. The difference between Example 2 and Example 1 is that, when performing the preparation step of the molybdenum disulfide nanotube-carbon nanotube hybrid material, Example 2 uses 0.876g of sodium molybdate dihydrate, 1.03g of thiourea, 0.235g of manganese chloride tetrahydrate and 0.125g of multi-walled carbon nanotubes.
[0036] Example 3 Example 3 of the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material. The difference between Example 3 and Example 1 is that, when performing the preparation step of the molybdenum disulfide nanotube-carbon nanotube hybrid material, Example 3 uses 0.766g of sodium molybdate dihydrate, 0.901g of thiourea, 0.205g of manganese chloride tetrahydrate and 0.167g of multi-walled carbon nanotubes.
[0037] Example 4 Example 4 of the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material. The difference between Example 4 and Example 1 is that, when performing the preparation step of the molybdenum disulfide nanotube-carbon nanotube hybrid material, Example 4 uses 0.5825g of sodium molybdate dihydrate, 0.685g of thiourea, 0.156g of manganese chloride tetrahydrate and 0.25g of multi-walled carbon nanotubes.
[0038] Example 5 Example 5 of the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material. The difference between Example 5 and Example 1 is that, when performing the preparation step of the molybdenum disulfide nanotube-carbon nanotube hybrid material, Example 5 uses 0.389g of sodium molybdate dihydrate, 0.458g of thiourea, 0.104g of manganese chloride tetrahydrate and 0.33g of multi-walled carbon nanotubes.
[0039] Example 6 Example 6 of the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material. The difference between Example 6 and Example 1 is that when performing the preparation step of the molybdenum disulfide nanotube-carbon nanotube hybrid material, Example 6 uses 0.291g of sodium molybdate dihydrate, 0.343g of thiourea, 0.078g of manganese chloride tetrahydrate and 0.375g of multi-walled carbon nanotubes.
[0040] Example 7 Example 7 of the present application provides a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material. The difference between Example 7 and Example 1 is that when performing the preparation step of the molybdenum disulfide nanotube-carbon nanotube hybrid material, Example 7 uses 0.233g of sodium molybdate dihydrate, 0.274g of thiourea, 0.062g of manganese chloride tetrahydrate and 0.4g of multi-walled carbon nanotubes.
[0041] Comparative Example 1 Comparative Example 1 provides a polyetheretherketone, which is prepared by the following steps: accurately weigh 100g of polyetheretherketone powder. Add the polyetheretherketone powder to ethanol, ultrasonically disperse it for 15min and place it on a magnetic stirrer, stir it at a speed of 600rpm for 3h, and then dry it at 80℃ for 4h and at 100℃ for 2h. Add the polyetheretherketone powder to a ball mill and ball mill it at 300rpm for 4h, and then dry it in a drying oven at 120℃ for 3h. Place the polyetheretherketone powder in a mold, maintain the pressure for 1h at a temperature of 360℃ and a pressure of 7MPa, and hot press it to obtain polyetheretherketone.
[0042] Comparative Example 2 Comparative Example 2 provides a carbon nanotube-polyetheretherketone composite material, which is prepared by the following steps: adding multi-walled carbon nanotubes to an auxiliary solvent (mixed by 30 mL of water, 10 mL of anhydrous ethanol and 4 mL of oleic acid), stirring for 30 minutes, maintaining stirring and ultrasonic treatment for 20 minutes to obtain a mixed solution. The mixed solution is poured into a 100 mL reactor and heated to 220°C at a rate of 1°C / min, maintained at the temperature for 24 hours, and then slowly cooled to room temperature at a rate of 0.4°C / min, filtered and washed, and the treated multi-walled carbon nanotubes are set aside.
[0043] Accurately weigh 98g of polyetheretherketone powder and 2g of multi-walled carbon nanotubes. Add polyetheretherketone powder and multi-walled carbon nanotubes to ethanol, ultrasonically disperse for 15 minutes and place on a magnetic stirrer, stir at 600rpm for 3h, then dry at 80℃ for 4h and at 100℃ for 2h to obtain a mixture. Add the mixture to a ball mill and ball mill at 300rpm for 4h, then dry in a drying oven at 120℃ for 3h to obtain a mixture, place the mixture in a mold, maintain pressure at 360℃ and 7MPa for 1h, and hot press to obtain a carbon nanotube-polyetheretherketone composite material.
[0044] Comparative Example 3 Comparative Example 3 provides a molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material, which is prepared by the following steps: Preparation of molybdenum disulfide nanoflower-carbon nanotube hybrid material: 0.2247g of ammonium molybdate tetrahydrate, 0.4494g of thiourea and 0.0281g of hexadecyltrimethylammonium bromide are added to 40mL of deionized water as molybdenum precursor, sulfur precursor and surfactant respectively, stirred for 30min, and then 0.33g of multi-walled carbon nanotubes (MWCNTs) are added, stirred and ultrasonically treated for 20min to obtain a mixed solution. The mixed solution is poured into a 100mL reactor for a hydrothermal reaction, and the reaction parameters are as follows: heating to 220°C at a rate of 1°C / min, maintaining the temperature for 24h, and then slowly cooling to room temperature at a rate of 0.4°C / min, filtering and washing to obtain a molybdenum disulfide nanoflower-carbon nanotube hybrid material.
[0045] Preparation of MoS2 nanoflower-carbon nanotube-polyetheretherketone composite material: Accurately weigh 98g polyetheretherketone powder and 2g MoS2 nanoflower-carbon nanotube hybrid material. Add the polyetheretherketone powder and MoS2 nanoflower-carbon nanotube hybrid material to ethanol, ultrasonically disperse for 15min and place on a magnetic stirrer, stir at 600rpm for 3h, then dry at 80℃ for 4h and at 100℃ for 2h to obtain a mixture. Add the mixture to a ball mill and ball mill at 300rmp for 4h, then dry in a drying oven at 120℃ for 3h to obtain a mixture, place the mixture in a mold, maintain pressure at 360℃ and 7MPa for 1h, and hot press to obtain a MoS2 nanoflower-carbon nanotube-polyetheretherketone composite material.
[0046] Test and Inspection (1) Scanning electron microscope imaging was performed on the molybdenum disulfide nanotube-carbon nanotube hybrid material in Example 5 and the molybdenum disulfide nanoflower-carbon nanotube hybrid material in Comparative Example 3, and the scanning electron microscope images were as follows: Figure 1 and Figure 2 shown.
[0047] (2) The compression performance test of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials prepared in Examples 1-7, the polyetheretherketone of Comparative Example 1, the carbon nanotube-polyetheretherketone composite material of Comparative Example 2, and the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Comparative Example 3 was carried out on a universal testing machine according to ISO 604:2002, with a sample size of 10×10×4 mm and a test condition of 1 mm / min. The test results are shown in Table 1 below.
[0048] (3) The surface hardness of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials prepared in Examples 1-7, the polyetheretherketone of Comparative Example 1, the carbon nanotube-polyetheretherketone composite material of Comparative Example 2, and the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Comparative Example 3 was tested on a Shore hardness tester in accordance with ISO 868. The sample size was 20×10×4 mm. The test results are shown in Table 1 below.
[0049] Table 1:
[0050] (4) A ball-disk reciprocating friction test was performed on the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials prepared in Examples 1-5, the polyetheretherketone of Comparative Example 1, and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2 on an Rtec friction and wear testing machine. A GCr15 steel ball with a diameter of 6.3 mm was reciprocated against the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material of 20×10×4 mm. The test conditions were as follows: load 80 N, time 30 min, speed 6 Hz (linear speed 96 mm / s). The test results are shown in Table 2 below.
[0051] Table 2:
[0052] Results Analysis The following is a combination of the experimental data provided in Table 1-2 and Figure 1-2 , describe this application in detail.
[0053] The molybdenum disulfide nanotube-carbon nanotube hybrid materials in Examples 1-7 of the present application are all multi-walled carbon nanotubes tightly wrapped on the molybdenum disulfide nanotube structure to successfully form a molybdenum disulfide nanotube-carbon nanotube hybrid structure, wherein the molybdenum disulfide nanotube-carbon nanotube hybrid material in Example 5 is as follows Figure 1 As shown, Figure 1 (a) It can be seen that the multi-walled carbon nanotubes and MoS2 nanotubes in the MoS2 nanotube-CNT hybrid material form a tight three-dimensional network structure as a whole. Figure 1 (b) It can be seen that the multi-walled carbon nanotubes are interwoven and wrapped around the molybdenum disulfide nanotubes and are densely distributed.
[0054] Referring to Table 1, the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials of Examples 1-7 are significantly improved in compressive strength and surface hardness compared with the polyetheretherketone of Comparative Example 1 and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2. It is shown that the addition of molybdenum disulfide nanotube-carbon nanotube hybrid materials is beneficial to improving the mechanical properties of polyetheretherketone and its composite materials. In particular, when the weight ratio of sodium molybdate dihydrate to multi-walled carbon nanotubes is 1.18:1, the compressive strength of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material of Example 1 is increased by about 23.77% (from 149.3MPa to 184.79MPa) compared with the polyetheretherketone of Comparative Example 1, and the surface hardness is also increased by 5.36% (from 85.5HD to 90.08HD), and the compressive strength and surface hardness of the carbon nanotube-polyetheretherketone composite material of Comparative Example 2 are also greatly improved. This indicates that the molybdenum disulfide nanotube structure and the carbon nanotube structure in the molybdenum disulfide nanotube-carbon nanotube hybrid material prepared by regulating the ratio of molybdenum precursor and carbon nanotubes in the range of 0.5-10:1 have a synergistic effect in improving the mechanical properties of the polyetheretherketone-based composite material.
[0055] Referring to Table 2, the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials of Examples 1-7 all exhibited lower friction coefficients and better wear resistance in friction and wear experiments compared to the polyetheretherketone of Comparative Example 1 and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2. In particular, when the weight ratio of sodium molybdate dihydrate to multi-walled carbon nanotubes was 1.18:1, the friction coefficient of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material of Example 1 was reduced by about 23.73% (from 0.295 to 0.225) compared to the polyetheretherketone of Comparative Example 1, and the wear resistance was improved by 88.95% (the wear loss was from 54.83×10-6 mm 3 / N·m is reduced to 6.06×10-6 mm 3 / N·m), and the friction reduction and wear resistance of the carbon nanotube-polyetheretherketone composite materials of Examples 1-7 are also greatly improved compared with that of Comparative Example 2. This shows that the molybdenum disulfide nanotube structure and the carbon nanotube structure in the molybdenum disulfide nanotube-carbon nanotube hybrid material prepared by adjusting the ratio of the molybdenum precursor and the carbon nanotube to 0.5-10:1 have a synergistic effect in improving the tribological properties of the polyetheretherketone-based composite material.
[0056] In summary, the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite materials of Examples 1-7 have significant advantages in mechanical properties and tribological properties compared to the polyetheretherketone of Comparative Example 1 and the carbon nanotube-polyetheretherketone composite materials of Comparative Example 2. The analysis is that the molybdenum disulfide nanotube-carbon nanotube hybrid material formed by molybdenum disulfide nanotubes and multi-walled carbon nanotubes provides an effective stress transfer network for the polyetheretherketone matrix, and the molybdenum disulfide nanotube structure and the multi-walled carbon nanotube structure in the molybdenum disulfide nanotube-carbon nanotube hybrid material are hollow tubular structures, which are beneficial to further improve the lubrication performance of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material. Under the synergistic effect of the molybdenum disulfide nanotube structure and the multi-walled carbon nanotube structure in the molybdenum disulfide nanotube-carbon nanotube hybrid material, the mechanical properties and tribological properties of the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material are simultaneously improved.
[0057] Further, see Figure 2 In the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of comparative example 3, the molybdenum disulfide nanoflowers are connected by multi-walled carbon nanotubes to form a molybdenum disulfide nanoflower-carbon nanotube hybrid material. The molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of comparative example 3 is used as a control. Figure 1 The ratio of molybdenum disulfide nanotubes to carbon nanotubes in the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material of Example 5 is equivalent to the ratio of molybdenum disulfide nanoflowers to carbon nanotubes in the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Comparative Example 3, but the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material of Example 5 is superior to the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Comparative Example 3 in terms of both mechanical properties (compression properties and surface hardness) and tribological properties (wear resistance). Moreover, the compression properties, surface hardness and wear resistance of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite materials of Examples 3-5 are superior to those of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material of Comparative Example 3, indicating that the weight ratio of sodium molybdate dihydrate to multi-walled carbon nanotubes is 1-5:1, which is conducive to further improving the mechanical properties and wear resistance of the molybdenum disulfide nanoflower-carbon nanotube-polyetheretherketone composite material.
[0058] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material, characterized in that: The invention is prepared from the following components in parts by weight: 97-99 parts of polyetheretherketone and 1-3 parts of molybdenum disulfide nanotube-carbon nanotube hybrid material.
2. The molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 1, characterized in that: The molybdenum disulfide nanotube-carbon nanotube hybrid material is prepared by the following steps: a precursor, a template agent, an auxiliary solvent and carbon nanotubes are mixed and then subjected to a hydrothermal reaction.
3. The molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 2, characterized in that: The precursor comprises a molybdenum precursor and a sulfur precursor in a weight ratio of 0.8-0.9:
1.
4. The molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 3, characterized in that: The weight ratio of the molybdenum precursor to the carbon nanotubes is 0.5-10:
1.
5. The molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 3, characterized in that: The weight ratio of the template to the molybdenum precursor is 1:3.7-3.
8.
6. The molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 2, characterized in that: The auxiliary solvent includes water, ethanol and oleic acid in a volume ratio of 7-8:2-3:
1.
7. The molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 2, characterized in that: The template agent includes one or more of manganese chloride tetrahydrate, manganese sulfate, and manganese nitrate.
8. A method for preparing the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The molybdenum disulfide nanotube-carbon nanotube hybrid material, polyetheretherketone powder and a solvent are mixed and ultrasonically dispersed and then dried to obtain a mixture, the mixture is ball-milled and then dried, and finally hot-pressed to obtain the molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material.
9. The method for preparing a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 8, characterized in that: The ball milling speed is 200-400 rpm, and the ball milling time is 3-5 hours.
10. The method for preparing a molybdenum disulfide nanotube-carbon nanotube-polyetheretherketone composite material according to claim 8, characterized in that: The temperature of the hot pressing molding is 350-370° C., the pressure is 5-10 MPa, and the holding time is 0.5-1.5 h.
Citation Information
Patent Citations
Nanometer hybrid material-modified epoxy resin self-lubricating composite coating layer and preparation method thereof
CN108753106A
MoS2 / carbon nanotube composite film and preparation method and application thereof
CN115249762A
Lubricating wear-resistant bearing bush and preparation method thereof
CN118931104A
Composite coating containing carbon / molybdenum disulfide nanometer tube and its preparation
CN1644763A
Low friction and low wear polymer / polymer composites
US20060030681A1